2017
DOI: 10.3390/su9030475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waste-to-Energy Plants on China’s Urbanization: Evidence from a Hedonic Price Analysis in Shenzhen

Abstract: Abstract:Along with the accelerated process of China's urbanization, the increasing urban population has put much pressure on solid waste disposal. A speeding-up development plan of waste incineration power generation has been launched in China, which aims to resolve the dilemma where many cities are besieged by waste. However, due to the potential impact on surrounding environment, the site selection of these facilities has encountered protests from local residents. The economic reflection of the non-market p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 52 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…YEAR is a significant and negative characteristic in the model and represents the age of the residential unit. This finding is consistent with those of studies in Shenzhen [64] and Beijing [26]. For housing unit building types in Beijing, the data showed that compared to slab and other building types, homebuyers dislike tower buildings.…”
Section: Impact Of Housing Characteristics On Housing Pricessupporting
confidence: 82%
“…YEAR is a significant and negative characteristic in the model and represents the age of the residential unit. This finding is consistent with those of studies in Shenzhen [64] and Beijing [26]. For housing unit building types in Beijing, the data showed that compared to slab and other building types, homebuyers dislike tower buildings.…”
Section: Impact Of Housing Characteristics On Housing Pricessupporting
confidence: 82%
“…WTE facilities can be seen as one kind of LULU (locally unwanted land use), of which the benefits are usually broadly distributed, while most of the costs tend to be localised [44,45]. WTE facilities face considerable and strong opposition from the local communities in which they are situated because they have potential negative impacts (e.g., smell and dioxin release) on local residents' environments, health, or even property [14,46]. Protests against incinerators, or antiincinerator campaigns, have been documented in many countries/regions worldwide [47,48].…”
Section: Public Opposition Riskmentioning
confidence: 99%
“…Thus, land purchase is vital as one of the primary consideration factors for investors. In addition, the distance to the residential area from refuse incineration power plant should not only be in accordance with rules published, but get the permission of residents nearby [41].…”
Section: Analysis On the Decision Factors Of The Wte Plant Site Selecmentioning
confidence: 99%